As redes sociais como fator de engajamento nos telejornais : um estudo sobre o Repórter Brasil e o Jornal da Cultura - Moraes, Laura Martins de (2020)
The current work has been initiated with one purpose in mind that is to link preliminary research to real-world news media content, with a view to connecting the audience´s participation on social media to Tv News and the Public Tv Broadcasting, ensuring the outpts are discoverable. Such thing has been done aiming specifically two majors public Tv channels in Brazil, the "Repórter Brasil" and the "Jornal da Cultura" and their online content-taking in consideration also the impact the foreign media has on them. To accomplish this task, this paper focuses its analysis on how users and viewers participate in the news and the world of open communication while watching those news programmes available to view online via Facebook. The ultimate goal has been to scrutinize such public involvement, their comments and discussions, on the events and how internet-based spectators could determine the outcome of what´s on news for both local broadcast channels. In order to do that, the current research takes off making use of a categorical approach based on the quantitative and qualitative content analysis, according to Bardin´s perspective (BARDIN, 1977), using data sources from samples set to two periods from the same year (2019). The first sample focused its attention to the data available from 26th August to 30th August 2019, and the second from 25th November to 29th November 2019.